O ensino do futebol pelas abordagens táticas - Salles, Henrique Barbosa de Oliveira Ferreira (Universidade Federal de São Carlos, 2014)
The reason why Football was chosen as the subject of this study, was due to the great appreciation for this modality. For some time, the “dream of being a football player” was cultivated and very latent in my life, but for reasons of stature, I was unable to carry on this “dream”. At the University, in contact with studies about football, it became clear that the tactical aspect must prevail over the physical and technical aspect, that is, knowing how to read and interpret the game situations to respond in the most appropriate way to them is more important than that motor gestures and physical issues. And as Soccer is one of the elements of the Body Culture of Movement present in School Physical Education classes, it is the duty of the school to properly teach this modality, providing conditions for students, regardless of the desire to pursue a football career, to know how to interpret the game situations and make effective decisions before them, and for that it is necessary to break with a traditional teaching model, which prioritizes the motor gesture, and adopt a methodology that allows students to know how to read and interpret the game situations. The objective of my research is to analyze the quality of play of a 9th grade class in the individual, group and collective tactical dimensions, based on an intervention based on a didactic unit of Football based on Tactical Approaches. The present research will have as a methodological reference the Action Research. This methodology has as principles the observation of the object of study and the intervention to provide a change, which can be positive or negative. Action research starts from a social reality in order to modify this reality through pedagogical interventions, for this reason the integration of research and intervention is of fundamental importance. In this methodology, the researcher must constantly assume the role of researched and that of the group participant. For data collection, two instruments will be used, which are the diaries of classes and filming. And for data analysis we will use the Team Sports Performance Assessment Procedure (TSAP) tool, which aims to produce valid information to assess student performance in invasion sports. Classes were held with themes related to the tactical situations of football, and the application of TSAP was carried out in two moments, the first before the didactic unit classes and the second was after the end of this unit. From the data from the Class Diaries and the TSAP it was possible to identify an improvement in the quality of the students' game in the individual, group and collective tactical dimensions.
The teaching of soccer through tactical approaches
Keywords: Futebol, Educação Física Escolar, Ensino.; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM